Three-dimensional echocardiographic left ventricular strain analysis in Fabry disease: correlation with heart failure severity, myocardial scar, and impact on long-term prognosis - Marek, Josef; Chocholová, Barbora; Rob, Daniel; Paleček, Tomáš; Mašek, Martin; Dostálová, Gabriela; Linhart, Aleš (European heart journal. Cardiovascular Imaging, 2023)
AIMS: Fabry disease (FD) is a multisystemic lysosomal storage disorder caused by a defect in the alpha-galactosidase A gene that manifests as a phenocopy of hypertrophic cardiomyopathy. We assessed the echocardiographic 3D left ventricular (LV) strain of patients with FD in relation to heart failure severity using natriuretic peptides, the presence of a cardiovascular magnetic resonance (CMR) late gadolinium enhancement scar, and long-term prognosis. METHODS AND RESULTS: 3D echocardiography was feasible in 75/99 patients with FD [aged 47 ± 14 years, 44% males, LV ejection fraction (EF) 65 ± 6% and 51% with hypertrophy or concentric remodelling of the LV]. Long-term prognosis (death, heart failure decompensation, or cardiovascular hospitalization) was assessed over a median follow-up of 3.1 years. A stronger correlation was observed for N-terminal pro-brain natriuretic peptide levels with 3D LV global longitudinal strain (GLS, r = -0.49, P < 0.0001) than with 3D LV global circumferential strain (GCS, r = -0.38, P < 0.001) or 3D LVEF (r = -0.25, P = 0.036). Individuals with posterolateral scar on CMR had lower posterolateral 3D circumferential strain (CS; P = 0.009). 3D LV-GLS was associated with long-term prognosis [adjusted hazard ratio 0.85 (confidence interval 0.75-0.95), P = 0.004], while 3D LV-GCS and 3D LVEF were not (P = 0.284 and P = 0.324). CONCLUSION: 3D LV-GLS is associated with both heart failure severity measured by natriuretic peptide levels and long-term prognosis. Decreased posterolateral 3D CS reflects typical posterolateral scarring in FD. Where feasible, 3D-strain echocardiography can be used for a comprehensive mechanical assessment of the LV in patients with FD.
Keywords: tepový objem; Fabry disease; kontrastní látky; gadolinium; Humans; jizva; Heart Failure; Stroke Volume; srdeční selhání; funkce levé komory srdeční; echokardiografie; Contrast Media; Echocardiography; Gadolinium; 3D echocardiography; Female; Cicatrix; lidé; myocardial strain; reprodukovatelnost výsledků; heart failure; Fabryho nemoc; ženské pohlaví; Male; Reproducibility of Results; prognóza; dysfunkce levé srdeční komory; Ventricular Dysfunction, Left; cardiovascular magnetic resonance; mužské pohlaví; Fabry Disease; echokardiografie trojrozměrná; Prognosis; Echocardiography, Three-Dimensional; Ventricular Function, Left